Enhancing English Language Learning through ICT Integration: Innovations, Challenges, and Pedagogical Implications - Arriyani, Nurfisi; Hartono, Rudi; Fitriati, Sri Wuli; Pratama, Hendi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
ICT in English Language Teaching (ELT) has revolutionized language learning by allowing the students to become more active, interact frequently and assume more responsibility in their learning process. This study investigates the research question: How do EFL teachers demonstrate and integrate Technological Pedagogical Knowledge (TPK) and Pedagogical Content Knowledge (PCK) in ICT-supported English language instruction? Focusing on EFL instructors at a public university, the study employed a quantitative research design supported by a survey instrument that measured teachers’ self-reported TPK and PCK levels. Supplementary data were gathered through lesson plan evaluations and structured classroom observations to triangulate findings. Descriptive statistical analysis has been conducted and provided in the form of mean scores and standard deviations in order to outline the centralities and ranges in the knowledge domains of teachers. Preliminary results show that teachers have reported to be above average when voicing their Pedagogical Content Knowledge (PCK) (M = 4.1, SD = 0.6), although their Technological Pedagogical Knowledge (TPK) (M = 3.4, SD = 0.9) scores have displayed more variance than the latter, which may show the necessity to provide more support to integrate the use of technology. There was a greater chance that a teacher having higher TPK would employ interactive and student-based ICT activities. In contrast, those with lower TPK relied more on traditional, lecture-based methods despite having access to digital tools. In order to promote balanced teacher professional knowledge (TPK) and pedagogical content knowledge (PCK) in EFL instructors, the results support the significance of focusing on professional development. This presentation provides evidence-based recommendations for teacher educators and policymakers to support the effective integration of ICT in tertiary-level English Language Teaching (ELT) settings.